A method for measuring the weight of a zinc plating layer based on a constant current dissolution method
Patent Information
- Application Number
- CN202611343918.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-27
AI Technical Summary
(1)该技术需要配置计算机及专用数据采集软件、恒流源、电解池组件(含专用测试夹具)及分析天平等多套设备,系统集成度高,整体造价通常在数万元以上,不适合中小企业和现场检测场景使用;
1.该基于恒流溶解法的镀锌层重量测量方法,单点测量时间通常在30~180秒,快于传统称重法和现有库仑法,适合快速检测和批量抽检。
Smart Images

Figure CN122983172A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal coating measurement technology, specifically to a method for measuring the weight of zinc coatings based on constant current dissolution. Background Technology
[0002] Galvanized steel sheets are widely used in construction, automobiles, home appliances and other fields due to their excellent corrosion resistance. The weight of the galvanized layer is one of the key indicators for measuring the quality of galvanized steel sheets, which directly affects the corrosion resistance and service life of the product. Therefore, accurate, fast and convenient measurement of the weight of the galvanized layer is of great significance for quality control and incoming material inspection.
[0003] Currently, the main methods for measuring the weight of galvanized coatings include gravimetric analysis, magnetic thickness measurement, X-ray fluorescence analysis, and coulometric analysis. Among these, the gravimetric analysis calculates the coating weight by measuring the weight difference of the sample before and after dissolving the coating. It has high accuracy but is cumbersome to operate and is a destructive or semi-destructive test. The magnetic thickness measurement method is simple to operate, but its accuracy is greatly affected by the substrate material and the uniformity of the coating. The X-ray fluorescence method has high accuracy, but the equipment is expensive and difficult to use in the field.
[0004] Coulometric method (electrolytic thickness measurement) is a method for measuring coating thickness based on Faraday's law of electrolysis. A search revealed that the closest prior art to this invention is patent CN106814126A (a method for testing the weight of a zinc coating and the distribution of trace elements within it). This patent uses the coulometric method based on Faraday's law to quantitatively measure the weight of the zinc coating. Its basic principle is as follows: a galvanized sheet sample is placed as the anode in an electrolytic cell along with an inert counter electrode. A constant direct current is applied between them, and the zinc layer on the surface of the galvanized sheet, acting as the anode, undergoes an electrochemical dissolution reaction (Zn→Zn²). + +2e - When the zinc layer is completely dissolved and the steel matrix is exposed, the voltage of the electrolytic cell changes abruptly. The dissolution endpoint is determined by monitoring and identifying the point of voltage change.
[0005] The core structure of this prior art includes: a constant current source module for outputting a constant DC current; an electrolytic cell assembly including an electrolytic cell, a dedicated test fixture, and an electrolyte solution; a potential monitoring module for real-time acquisition and recording of the voltage-time curve during the electrolysis process; a computer control system with a built-in data acquisition card and dedicated software to automatically display the dissolution curve and identify the inflection point of the curve; and an analytical balance for weighing the sample before and after dissolution.
[0006] However, this existing technology has the following problems and drawbacks when measuring the weight and thickness of the galvanized layer: (1) This technology requires multiple sets of equipment, including a computer and dedicated data acquisition software, constant current source, electrolytic cell components (including dedicated test fixtures) and analytical balance. The system has a high degree of integration and the overall cost is usually tens of thousands of yuan or more. It is not suitable for small and medium-sized enterprises and on-site testing scenarios. (2) According to the method disclosed in the patent, the sample needs to be cleaned, dried and weighed before and after the measurement. The steps are numerous and the single measurement takes a long time, making it difficult to achieve rapid detection. (3) This technology uses computer software to identify the inflection point of the voltage-time curve to determine the dissolution endpoint. It requires pre-setting sensitivity parameters and is sensitive to changes in ambient temperature. Changes in the measured potential may affect the accuracy of the endpoint determination. (4) This technology requires placing the sample into a special test fixture. The sample size must match the fixture. For large workpieces or irregularly shaped galvanized components, it is difficult to measure directly. (5) The equipment involved in this technology is large in size and requires an external power supply and computer. It is mainly suitable for laboratory environments and cannot meet the needs of rapid on-site assessment in scenarios such as construction sites, incoming material inspection or outdoor inspection. Summary of the Invention
[0007] To address the shortcomings of existing technologies, this invention provides a method for measuring the weight of galvanized layers based on constant flow dissolution, thus solving the problems mentioned in the background section.
[0008] To achieve the above objectives, the present invention provides the following technical solution: a method for measuring the weight of a zinc plating layer based on a constant current dissolution method, comprising the following steps: Step 1: Define the area: On the area to be tested on the galvanized sheet, use insulating tape to stick and cut out a measurement area of a fixed size, exposing the zinc layer to be dissolved; Step 2: Prepare the electrolytic cell: Add electrolyte solution dropwise to the exposed zinc layer area, ensuring the solution covers the measurement area without overflowing; Step 3: Connect the circuit: Connect the positive terminal of the constant current source to the galvanized plate as the anode, and connect the negative terminal of the constant current source to the inert electrode, which is inserted into the electrolyte; connect the current monitoring module in series in the circuit for real-time monitoring of the circuit current. Step 4, Electrolysis: Turn on the constant current source, adjust the current to the preset constant value, record the start time t0, keep the current constant, and observe the circuit current reading; Step 5: Determine the dissolution endpoint: When the zinc layer is completely dissolved and the steel substrate is exposed, the circuit current drops sharply. Record the termination time t1 of the current drop. Step 6: Calculate the weight per unit area of the zinc coating: According to Faraday's law of electrolysis, the mass of the dissolved zinc layer m is calculated using the constant current value I, the dissolution time Δt = t1 - t0, and the area of the measurement region A, according to the formula m = (M × I × Δt) / (n × F). Then, the weight ρ of the zinc coating per unit area is calculated using the formula ρ = m / A. Where M is the molar mass of zinc, n is the charge number of zinc ions, and F is the Faraday constant.
[0009] Furthermore, the insulating tape mentioned in step one is a polyimide tape, and the measurement area is a circular hole. The polyimide tape has excellent resistance to electrolyte corrosion and is not easily wetted and swollen by the electrolyte solution during electrolysis. It can stably isolate the zinc plating layer outside the test area, avoid additional electrolytic dissolution in non-test areas, and ensure the accuracy of the defined area. The circular hole has uniform stress at the edge, and is not prone to burrs or tears during the tape punching operation. The opening boundary is regular, which helps to ensure that the actual electrolytic area is consistent with the theoretically calculated area and reduces the measurement error introduced by the area.
[0010] Furthermore, the electrolyte solution mentioned in step two is a 3% NaCl aqueous solution. The 3% NaCl aqueous solution has moderate conductivity, is simple to prepare, and the raw materials are readily available. It has a moderate reaction rate for zinc layer dissolution, which can ensure the stable progress of the electrolysis process and avoid the difficulty in capturing the endpoint due to an excessively fast reaction rate. Under this electrolyte system, a passivation effect can be stably generated after the steel substrate is exposed, and the current drop signal is clear, making it easy for operators to identify the dissolution endpoint. It is suitable for the rapid on-site detection of most conventional zinc plating layers.
[0011] Furthermore, the electrolyte solution can also be selected from any of the following: 1-3 mol / L KCl aqueous solution, 5% Na2SO4 aqueous solution, 0.1 mol / L NH4Cl aqueous solution, or saturated NaCl aqueous solution. 1-3 mol / L KCl aqueous solution has a high potassium ion migration rate, better solution conductivity, lower circuit contact resistance, more stable current during electrolysis, and higher sensitivity of the endpoint signal. 5% Na2SO4 aqueous solution has a low chloride ion content, which can reduce corrosion of the steel substrate under non-test conditions, making it suitable for testing components sensitive to chloride ion corrosion. 0.1 mol / L NH4Cl aqueous solution can accelerate the anodic dissolution rate of the zinc layer, further shortening the single-point test time. Saturated NaCl aqueous solution has a high ion concentration, which can reduce the ohmic voltage drop of the electrolyte, making it suitable for measurement conditions of thicker zinc plating layers. Testers can flexibly select the appropriate solution based on the workpiece material, plating thickness, and site conditions.
[0012] Furthermore, the constant DC current output by the constant current source in step three should not exceed 100mA. If the current is too large, the electrolytic reaction will be too violent, the electrolyte will easily generate a lot of heat and bubbles will overflow, which will easily damage the stability of the droplet electrolytic cell and aggravate the occurrence of side reactions, interfering with the endpoint current drop signal. Limiting the DC current to within 100mA can control the intensity of the electrolytic reaction, suppress excessive heating and a large amount of gas evolution, maintain the electrolyte stably residing in the opening area, ensure the stability of the current-time signal, and help obtain reliable measurement results.
[0013] Furthermore, the inert electrode mentioned in step three is a graphite rod. Graphite rods have good chemical stability and are not prone to anodic oxidation and dissolution in the electrolysis system of this application. They will not introduce impurity ions into the electrolyte, and the electrode itself will not participate in the electrochemical reaction and be consumed. Graphite rods have excellent conductivity, low cost, are easy to process and shape, and can be used repeatedly, which is suitable for the needs of portable on-site detection.
[0014] Furthermore, the current monitoring module mentioned in step three is a digital multimeter, set to the DC current range, and connected in series in the circuit. The digital multimeter is a general-purpose portable instrument with intuitive readings, capable of providing real-time feedback on the circuit current. Connecting it in series in the circuit allows for accurate acquisition of the actual operating current of the entire electrolysis circuit, avoiding data distortion caused by parallel sampling.
[0015] Furthermore, the criterion for determining a sharp drop in current in step five is: the loop current drops sharply to below 10% of the initial current value. Setting this quantitative threshold can transform the subjective "sharp drop in current" into an executable objective judgment condition, avoiding the endpoint identification deviation caused by differences in subjective judgment by operators. When the zinc layer is completely dissolved and the substrate is passivated, the loop impedance increases significantly, and the current can stably drop below this threshold. This can be used as the basis for endpoint determination, improving the consistency and repeatability of test results under different operators and different working conditions.
[0016] Furthermore, in step five, after the circuit current suddenly drops, maintain the energized state and continue observing for 5-10 seconds. After confirming that the current no longer rises, record the termination time t1. This delayed observation is used to avoid misjudgments caused by instantaneous current drops due to local disturbances in the electrolyte and momentary contact jitter, and to eliminate false endpoints caused by signal glitches. If the zinc layer has not completely dissolved, a temporary current drop may occur due to local factors; the current will then rise again after 5 seconds. Continuous observation for 10 seconds confirms that the current remains at a low level and does not rebound, then the termination time is recorded, effectively reducing false triggering and further improving test reliability.
[0017] This invention provides a method for measuring the weight of zinc plating based on constant current dissolution, which has the following advantages: 1. This method for measuring the weight of galvanized layers based on constant flow dissolution typically takes 30 to 180 seconds for a single-point measurement, which is faster than traditional weighing methods and existing coulometric methods, making it suitable for rapid testing and batch sampling.
[0018] 2. This method for measuring the weight of galvanized layers based on constant flow dissolution does not require an analytical balance, the preparation of various chemical reagents, a computer, or specialized software. Ordinary workers can operate it after simple training, thus reducing the skill requirements for personnel.
[0019] 3. This method for measuring the weight of galvanized layers based on constant flow dissolution dissolves the zinc layer only within a limited small circular hole (5mm in diameter), which has minimal and acceptable impact on the overall workpiece. It is suitable for finished product inspection and incoming material inspection. At the same time, it does not require special test fixtures and can directly measure large workpieces or irregularly shaped galvanized components, thus having a wider range of applications. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the measurement method steps of the present invention. Detailed Implementation
[0021] The embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples. The following examples are for illustrative purposes only and should not be construed as limiting the scope of the invention.
[0022] This embodiment provides a method for measuring the weight of zinc plating based on constant current dissolution method. The specific steps are as follows: S1. Limited Area: Take a galvanized sheet sample, attach polyimide insulating tape to the area to be tested, and use a hole punch to make a circular hole with a diameter of 5mm, exposing the zinc layer to be dissolved. The area of the circular hole, A = π × (5 / 2)² ≈ 19.63 mm² = 1.963 × 10⁻⁶ mm². -5 m²; S2. Preparation of electrolytic cell: Add an appropriate amount of 3% NaCl aqueous solution as electrolyte solution into the circular hole, ensuring that the solution completely covers the area of the circular hole without overflowing; S3. Connecting the circuit: Connect the positive terminal of the constant current source to the galvanized plate as the anode; connect the negative terminal of the constant current source to the graphite rod as the inert counter electrode, and insert the graphite rod into the electrolyte in the round hole; set the digital multimeter to the DC current range (200mA range) and connect it in series in the circuit to monitor the current. S4. Electrolysis: Turn on the constant current source, adjust the current to 50mA (0.050A), and record the start time t0; keep the current constant and observe the multimeter current reading. S5. Determine the dissolution endpoint: When the zinc layer is completely dissolved and the steel substrate is exposed, the circuit current drops sharply due to the rapid passivation of the steel under anodic polarization. When the current drops sharply to less than 10% of the initial current value (50mA) (i.e., less than 5mA), the dissolution endpoint is determined to have been reached, and the termination time t1 is recorded. S6. Calculation: Assuming the dissolution time Δt = t1 - t0 = 120s, then according to Faraday's law of electrolysis: m=(65.38×0.050×120) / (2×96485)≈0.00203g Weight per unit area: ρ=m / A=0.00203 / (1.963×10 -5 )≈103.4g / m² That is, the weight of the zinc coating per unit area of the galvanized sheet is approximately 103.4 g / m².
[0023] The above calculation process can be completed manually by the operator, or it can be automatically calculated and the results displayed by a simple calculator or microcontroller.
[0024] Meanwhile, the electrolyte solution used in step S2 can be a 1 mol / L KCl aqueous solution. Potassium ions have a higher migration rate than sodium ions, which can improve the conductivity of the solution, make the current more stable, and make the endpoint determination more sensitive.
[0025] The electrolyte solution may also be any of the following: (1) 5% Na2SO4 aqueous solution: Sulfate ions are less corrosive to steel matrix than chloride ions, and are suitable for applications sensitive to chloride ions.
[0026] (2) 0.1 mol / L NH4Cl aqueous solution: Ammonium salt solution can improve the dissolution rate and is suitable for rapid measurement needs.
[0027] (3) Saturated NaCl aqueous solution: Extremely high concentrations can reduce contact resistance, but may accelerate electrode polarization.
[0028] Meanwhile, the determination of the dissolution endpoint in step S5 can be achieved by the bubble observation method: during the electrolytic dissolution process, tiny bubbles (oxygen) will be generated on the surface of the anode (galvanized sheet). When the zinc layer is completely dissolved and the steel substrate is exposed, the bubble generation rate will change significantly (usually decrease significantly). The operator can manually determine the endpoint by visually observing the changes in the bubbles. Furthermore, step S5 can also employ a potential indicator method: adding a potentiometer to the electrolyte solution to counteract the potential of Zn. 2+ Concentration-sensitive indicators (such as dithizone), when Zn 2+ The solution changes color when the concentration reaches the preset value, indicating the dissolution endpoint.
[0029] In addition, instead of using an independent adjustable DC constant current source in step S3, the resistance range (such as the 200Ω range) of a common digital multimeter is used as the constant current source. Many digital multimeters output a constant test current of about 1 to 3 mA when measuring in the resistance range. This function can be used as a miniature constant current source, which is suitable for measuring thinner zinc plating layers (with shorter dissolution time). At this time, another multimeter can still be connected in series in the circuit for current monitoring.
[0030] This invention is applied to the incoming inspection of galvanized steel components at construction sites. Inspectors arrive at the site carrying a portable constant current source (battery powered, adjustable output 0-100mA), a digital multimeter, graphite rod electrodes, insulating tape, and a small bottle of 3% NaCl solution. They directly measure the surface of large galvanized steel components: insulating tape is used to attach to the component surface, and a 5mm diameter hole is cut. Electrolyte is added, the circuit is connected, and electricity is applied to dissolve the galvanized layer. The dissolution time is recorded, and the weight per unit area of the galvanized layer is calculated on-site. No sampling or testing is required, enabling rapid on-site quantitative assessment.
[0031] In summary, by dissolving the zinc plating layer through constant current electrolysis and combining it with Faraday's law of electrolysis for calculation, quantitative measurement can be completed with only a constant current source and an ordinary multimeter. This invention solves the problems of expensive equipment, cumbersome operation, poor portability, and limitations on sample size in the prior art. It has the advantages of extremely simple equipment, low cost, easy operation, and fast measurement.
[0032] The embodiments of the present invention are given for illustrative and descriptive purposes only, and are not intended to be exhaustive or to limit the invention to the forms disclosed. Many modifications and variations will be apparent to those skilled in the art. The embodiments were chosen and described in order to better illustrate the principles and practical application of the invention, and to enable those skilled in the art to understand the invention and to design various embodiments with various modifications suitable for a particular purpose.
Claims
1. A method for measuring the weight of a zinc plating layer based on constant current dissolution, characterized in that, Includes the following steps: Step 1: Define the area: On the area to be tested on the galvanized sheet, use insulating tape to stick and cut out a measurement area of a fixed size, exposing the zinc layer to be dissolved; Step 2: Prepare the electrolytic cell: Add electrolyte solution dropwise to the exposed zinc layer area, ensuring the solution covers the measurement area without overflowing; Step 3: Connect the circuit: Connect the positive terminal of the constant current source to the galvanized plate as the anode, and connect the negative terminal of the constant current source to the inert electrode, which is inserted into the electrolyte; connect the current monitoring module in series in the circuit for real-time monitoring of the circuit current. Step 4, Electrolysis: Turn on the constant current source, adjust the current to the preset constant value, record the start time t0, keep the current constant, and observe the circuit current reading; Step 5: Determine the dissolution endpoint: When the zinc layer is completely dissolved and the steel substrate is exposed, the circuit current drops sharply. Record the termination time t1 of the current drop. Step 6: Calculate the weight per unit area of the zinc coating: According to Faraday's law of electrolysis, the mass of the dissolved zinc layer m is calculated using the constant current value I, the dissolution time Δt = t1 - t0, and the area of the measurement region A, according to the formula m = (M × I × Δt) / (n × F). Then, the weight ρ of the zinc coating per unit area is calculated using the formula ρ = m / A. Where M is the molar mass of zinc, n is the charge number of zinc ions, and F is the Faraday constant.
2. The method for measuring the weight of a zinc plating layer based on constant current dissolution method according to claim 1, characterized in that: The insulating tape mentioned in step one is polyimide tape, and the measuring area is a circular hole.
3. The method for measuring the weight of a zinc plating layer based on constant current dissolution method according to claim 1, characterized in that: The electrolyte solution mentioned in step two is a 3% NaCl aqueous solution.
4. The method for measuring the weight of a zinc plating layer based on constant current dissolution method according to claim 1, characterized in that: The electrolyte solution may also be selected from any of the following: 1-3 mol / L KCl aqueous solution, 5% Na2SO4 aqueous solution, 0.1 mol / L NH4Cl aqueous solution, or saturated NaCl aqueous solution.
5. The method for measuring the weight of a zinc plating layer based on constant current dissolution method according to claim 1, characterized in that: The constant DC current output by the constant current source in step three shall not exceed 100mA.
6. The method for measuring the weight of a zinc plating layer based on the constant current dissolution method according to claim 1, characterized in that: The inert electrode mentioned in step three is a graphite rod.
7. The method for measuring the weight of a zinc plating layer based on the constant current dissolution method according to claim 1, characterized in that: The current monitoring module mentioned in step three is a digital multimeter, set to the DC current range, and connected in series in the circuit.
8. The method for measuring the weight of a zinc plating layer based on constant current dissolution method according to claim 1, characterized in that: The criterion for determining a sharp drop in current in step five is: the loop current drops sharply to less than 10% of the initial current value.
9. The method for measuring the weight of a zinc plating layer based on constant current dissolution method according to claim 1, characterized in that: In step five, after the circuit current drops sharply, keep the circuit powered on and observe for 5 to 10 seconds. Once the current is confirmed to no longer rise, record the termination time t1.
Citation Information
Patent Citations
Testing method for weight of zinc coating and distribution of trace elements in zinc coating
CN106814126A